Understanding Fifth Generation Communication and Internet of Things (IoT) - Kaul, Siddarth; Jain, Anuj; Saini, Rajesh (Indian Journal of Computer Science, 2018)
The paper proposes to clearly elaborate the usefulness and necessity of IoT (Internet of Things) with 5G Communication. It is clearly known that the next generation networks and standards combine communication and computing together to put forward intelligent communication for the next generation. IoT (Internet of Things) requires extra care for its design from its various hardware of small objects, physical system, and network architecture. Various solutions of IoT (Internet of Things) have evolved from the traditional wireless networks and actuators and M2M communication in mission critical applications. The main aim of the paper is to understand the mission critical communication and availability and reliability of different smart objects in 5G communication by helping leverage the various key technology enablers like air interface and network architecture to help provide an overview to this new technology under development.